De la indulgencia a la condena: la responsive regulation en el régimen de fiscalización ambiental en Perú - Gamarra Abarca, Sebastian (2019)
The influence of the Responsive Regulation Theory in administrative law and, especially, in the areas associated with environmental management has brought into debate both the redefinition of the role of regulatory agencies and the relevance of an increasingly dominant persuasive approach as an alternative to the repressive character of law.In this article, the author seeks to examine the postulates of the Ayres and Braithwaite’s theory and, using several legal instruments among wich stands out the new Monitoring Regulation, analyze its reception in the regulatory policy of the Environmental Monitoring and Assesment Agency (Spanish: OEFA).